The valuation of companies as a strategy for the efficiency in the management of their assets - Riascos Araujo, Andrés Darío; Sáenz Córdoba, Jairo (SATHIRI, 2019)
The purpose of this article is to identify the need to assess a company to know its benefits and be clear about their different quantitative and qualitative analyzes that involve in order to obtain adequate results. The evaluation methodology of the company is Discounted Free Cash Flow, in which, the net present value of the projected cash flows in a given scenario is calculated, plus the value in perpetuity, this value is added investments and assets not operational if it exists. To obtain the equity value, the amount of the financial debt must be deducted from the value of the company. In this case the assessment is carried out at the company KAN BAN Consultants established as one of the technology-based companies in Nariño specialized in strategic consulting on issues of quality, an activity with much market, not only at the local level but also at the national level and whose financial value in the market is given by the degree positioning of its goodwill resulting the intangible heritage of greater value after the organizational knowledge present in its human talent. Therefore, it must be recognized that, in addition to the growth opportunities that the market offers these companies, economic activities requires a significant financial leverage that can be obtained through legal and financial structures that allow the issuance of shares, for which it is essential to be clear about the financial valuation of the company. For this reason, it becomes necessary for the company to deal with estimate the financial value of market, while its position as one of the pioneering companies in the strategic consulting services in quality at the level of the municipality of Pasto, and at the level of Nariño make it susceptible of being acquired by a much larger consulting company or even enter to processes of fusion with consulting firms in administrative issues in the region.